ПРОФЕССИОНАЛЬНО-ЗНАЧИМЫЕ КАЧЕСТВА ПСИХОЛОГА КАК ФАКТОР ЭФФЕКТИВНОЙ ДЕЯТЕЛЬНОСТИ - Нурымбетова, Э.Ж. (SCIENCE and SOCIETY, 2023)
Theoretical analysis of professionally significant features and modern requirements for psychologist’s activity as a factor of psychologist’s effective activity is given in the paper.